Surviving black swans: The challenge of market timing systems - Pankaj Topiwala; Wei Dai (Journal of Risk and Financial Management, 2022)
It is an open secret that most investment funds actually underperform the market. Yet, millions of individual investors fare even worse, barely treading water. Algorithmic trading is now so common, it accounts for over 80% of all trades and is the domain of professionals. Can it also help the small investor? Individual investors are advised to buy-and-hold an index fund or a balanced portfolio including stocks, bonds, and cash equivalents. That would ensure market performance. However, market indices also occasionally have deep drawdowns (such as the devastating market crash of 1929 and other so-called Black Swan events). In contrast to received wisdom, we argue with evidence from backtesting on major U.S. market indices, as well as some select stocks that simple ideas in rule-based market timing can in fact be useful. One can not only obtain good results, but outperform market indices, while, at the same time, reducing deep drawdowns, surviving Black Swan events.
Keywords: 650; algorithm trading; buy-and-hold; index trading; investment; market timing; trading